2017
DOI: 10.1177/2332649217748428
|View full text |Cite
|
Sign up to set email alerts
|

Is Love Color-blind? Racial Blind Spots and Latinas’ Romantic Relationships

Abstract: The racial stratification literature is rife with examples of how color-blindness has become a dominant ideology among Whites to deny the continuing significance of race at work, school, and in everyday life. Less understood are the racial ideologies deployed by people of color. Drawing on 20 in-depth interviews, we examine how college-educated Latinas acknowledge or deny the significance of race and racial hierarchies in decisions about whom to date. We find Latinas who stated an openness to dating men of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Further, Hermann and Campbell (2012) found that even when individuals express positive attitudes toward interracial relationships, these attitudes neither systematically align with individual practices nor do they equate to intermarriage. It appears that clear racial preferences underlie colorblind attitudes toward relationships (Muro and Martinez 2018).…”
Section: Religion and Interracial Relationshipsmentioning
confidence: 99%
“…Further, Hermann and Campbell (2012) found that even when individuals express positive attitudes toward interracial relationships, these attitudes neither systematically align with individual practices nor do they equate to intermarriage. It appears that clear racial preferences underlie colorblind attitudes toward relationships (Muro and Martinez 2018).…”
Section: Religion and Interracial Relationshipsmentioning
confidence: 99%